Aryldiazonium Salts and DABSO: A Versatile Combination for Three‐Component Sulfonylative Cross‐Coupling Reactions. Issue 11 (19th April 2022) - Das, Pritha; Das, Subhodeep; Jana, Ranjan
Abstract: A combination of aryldiazonium salts and DABSO provides a unique opportunity for sulfonylative multicomponent cross‐coupling reactions. Here, a copper‐catalyzed three‐component cross‐coupling of aryldiazonium salts, DABSO with arylboronic acids to obtain medicinally relevant unsymmetrical diarylsulfones is disclosed. Interestingly, a catalyst‐free approach for the synthesis of arylvinylsulfones from the corresponding vinyl boronic acids or vinyl halides is explored under basic condition. Tethered aryldiazonium salts provided the corresponding annulated alkylvinylsulfones via alkene difunctionalization under the same transition metal‐free condition. Mechanistically, these multicomponent reactions proceed through a single electron pathway by the formation of arylsulfonyl radical as a key intermediate. Abstract : A catalyzed synthesis of diarylsulfones with arylboronic acids and catalyst‐free synthesis of arylvinyl and alkylvinyl sulfones from vinyl bronic acids or halides is reported.